Not Just Another Assessment Method: Reimagining Environmental Flows Assessments in the Face of Uncertainty - Horne, Avril C.; Webb, J. Angus; Mussehl, Meghan; John, Andrew; Rumpff, Libby; Fowler, Keirnan; Lovell, Daniel; Poff, LeRoy (Frontiers in Environmental Science, 2022)
Adaptive management has become the preferred approach for managing environmental flows globally, and successful implementation recognizes multiple dimensions of variability and complexity in socio-ecological systems. This paper outlines an environmental flow assessment methodology that explicitly addresses the uncertainty and change inherent in adaptively managing multiple values for management of environmental flows. While non-stationarity and uncertainty are well recognised in the climate literature, these have not been addressed within the structure of environmental flows methodologies. Here, we present an environmental flow assessment that is structured to explicitly consider future change and uncertainty in climate and socio-ecological values, by examining scenarios using ecological models. The environmental flow assessment methodology further supports adaptive management through the intentional integration of participatory approaches and the inclusion of diverse stakeholders. We present a case study to demonstrate the feasibility of this approach, highlighting how this methodology facilitates adaptive management. Rethinking our approach to environmental flows assessments is an important step in ensuring that environmental flows continue to work effectively as a management tool under climate change.